Hydatid Disease of liver communicating with common bile duct managed by ERCP - A case report - Jha, Anurag; Pathak, Rahul; Sharma, Sashi; Khadga, Prem (Journal of Advances in Internal Medicine, 2017)
Cystic hepatic disease is common in Asia, South America and Africa. Rupture of the hydatid cyst into the biliary tree can lead to serious cholangitis. In this report, a 53-year-old lady presented with the signs and symptoms of obstructive jaundice and cholangitis. Ultrasonography reported dilated common bile duct(CBD) with sludge and hydatid cysts in the liver. CECT revealed large cysts with enhancing thin wall in left and right lobe of liver with communicating into CBD and right IHBD respectively and features of obstructive biliopathy. Due to signs and symptoms of obstructive jaundice in addition to lab data and imaging modalities, ruptured hydatid cyst into the biliary tree was considered, and ERCP intervention was performed, after endoscopic sphincterotomy , membranes of the cysts were extracted. Post intervention, signs and symptoms and cholestasis enzymes subsided. Journal of Advances in Internal Medicine Vol.5(2) 2016: 38-40